ANALISIS HUBUNGAN PERSEPSI KONSUMEN PADA APLIKASI BAURAN PEMASARAN TERHADAP LOYALITAS KONSUMEN (CARREFOUR HYPERMARKET LEBAK BULUS) - Angriyani Hutapea (2013)
This study aims to determine and prove the significant influence of the marketing mix (product, price, place and promotion) on consumer loyalty Carrefour Lebak fleeced. By using multiple regression analysis. Sample was taken from the students of UPN "VETERAN JAKARTA" because the object under study ever or often berebelanja in Carrefour Lebak Bulus so it deserves to be investigated. By using SPSS 21. This study used a sample of 130 respondents, 30 and 100 research trials. The results showed that the product, price, place and promotion have strong relationships and positive impact on customer loyalty. The results achieved in this study is expected to be a material consideration for the company's progress and useful for writers as well as those reading this paper.